Sexuality, adolescence and sexual education - Balarezo-Lòpez, Gunther Naldo (2024)
Currently, sexuality continues to be a taboo topic with many myths surrounding it, so sexual education must be partof the training of every human being, especially in adolescence, given that at this stage many doubts arise, questions andqueries on different topics. In many cases, the information that adolescents have from peers, school, the media, and theinternet is distorted. Although the family should be the place where children are trained on this topic, parents do not feelprepared for it for different reasons since they do not have the appropriate knowledge to be able to answer the questions oftheir adolescent children.